IMPLEMENTASI MIKROKONTROLER SEBAGAI PENCACAH FREKUENSI BERBASIS PENGUKURAN PERIODE ISYARAT MASUKAN - Freddy Kurniawan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2009)
One of the main components from frequency counter is a processor. This processor must have ability to conduct counting and arithmetical calculation. To get competitive price, in this research a microcontroller is applied as a processor. This paper presents design of frequency counter based on microcontroller AT89S51 which has two independent timers. The input frequency counter is conducted by using facilities inside microcontroller e.g. T0 and external interruption. Counter method used in this research is by measuring input signal period. This method is proven effectively to count frequency especially low frequency. As the result, the frequency counter has successfully measured frequency from 0.1 until 10 kHz with maximum error 1%. This device is possible to be the next frequency counter with competitive price.